Accelerated C# 2010 - Nash, Trey.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
C# 2010 offers powerful new features, and this book is the fastest path to mastering them$1 (Band the rest of C#$1 (Bfor both experienced C# programmers moving to C# 2010 and programmers moving to C# from another object-oriented language. Many books introduce C#, but very few also explain how to use it optimally with the .NET Common Language Runtime (CLR). This book teaches both core C# language concepts and how to wisely employ C# idioms and object-oriented design patterns to exploit the power of C# and the CLR. This book is both a rapid tutorial and a permanent reference. You'll quickly master C# syntax while learning how the CLR simplifies many programming tasks. You$1 (Bll also learn best practices that ensure your code will be efficient, reusable, and robust. Why spend months or years discovering the best ways to design and code C# when this book will show you how to do things the right way from the start? Comprehensively and concisely explains both C# 2008 and C# 2010 features Focuses on the language itself and on how to use C# 2010 proficiently for all .NET application development Concentrates on how C# features work and how to best use them for robust, high-performance codes
C# Preview -- C# and the CLR -- C# Syntax Overview -- Classes, Structs, and Objects -- Interfaces and Contracts -- Overloading Operators -- Exception Handling and Exception Safety -- Working with Strings -- Arrays, Collection Types, and Iterators -- Delegates, Anonymous Functions, and Events -- Generics -- Threading in C# -- In Search of C# Canonical Forms -- Extension Methods -- Lambda Expressions -- LINQ: Language Integrated Query -- Dynamic Types.
Keywords: Computer science; Computer Science; Programming Languages, Compilers, Interpreters